PENAMBAHAN SENAM OTAK PADA PROGRAM SENAM SEHAT ANAK INDONESIA (SSAI) DAPAT MENINGKATKAN MEMORI JANGKA PENDEK DAN INDEKS KESEGARAN JASMANI SISWA SD INPRES PONDANG - Joanne Ingrid Robot; I Nyoman Adiputra; S. Indra Lesmana; Dewa Putu Sutjana; I Putu Adiartha Griadhi; M. Ali Imron (Sport and Fitness Journal, 2019)
ABSTRACTBackground: Short-term memory plays a role in all children's cognitive processes both in understanding the language, working on the task and problem-solving process. The speed of cognitive processes in children depend on the degree of activation of short-term memory. With stimulation that given in the form of brain-activating movements is expected to integrate short-term memory and long-term memory to generate new knowledge or expand the existing load in long-term memory. Cognitive function and academic achievement can also be influenced by the level of physical fitness. Physical fitness is very useful to support the physical capacity of children who in the end expected to improve his performance. Objective: This research was conducted to find out how big increase of short-term memory and physical fitness at the addition of Brain Gym in SSAI program at elementary school student of Inpres Pondang. Method: This research is true experimental, using two group pre and post test control group design. This research was conducted at SD Inpres Pondang, 3 times weekly for 6 weeks, at January 22, 2018 - March 05, 2018. The sample of research is 42 people divided into two groups. The Control Group in the form of SSAI program and the Treatment Group was given the addition of Brain Gym in the SSAI program. The measuring instrument used to memory span to measure short-term memory and TKJI to measure physical fitness. Results: The results of hypothesis testing using Wilcoxon test and Mann Whitney test. Wilcoxon test results showed short-term memory improvement in the treatment group significantly (p<0.05), the control group showed significant short-term memory increase (p<0.05). The result of hypothesis test shows the value of increase of physical fitness index in the treatment group significantly (p<0.05). The increase value of physical fitness index in control group significantly (p<0.05). Mann Whitney test results showed the value of span digits in the treatment group and control group with p=0.005 (p<0.05). Physical fitness value in treatment group and control group with p value = 0.091 (p>0.05). Conclusion: Statistically there is a difference in the addition of brain gymnastics to SSAI in increasing short-term memory of elementary students. Statistically there is no difference in the addition of brain gymnastics in SSAI in improving physical fitness in elementary school students.Keywords: Short term memory, physical fitness, memory span, Indonesian physical fitness test, brain gym, healthy gymnastics Indonesian children.